Getting God Through Music. Issue 3 (July 2018) - Stancliffe, David
Abstract : This article distinguishes between 'the what' and 'the how' of music and worship, of life itself, to stress that it is not what we do but how we do it that reveals what we are being shaped to become. Good worship is what happens when we try out – rehearse – what we are really supposed to be. 'Christian' is not a what that we are but a way (a how ) we are becoming what we are destined for. Taking communal singing as an example, I illustrate how music-making can help us 'get' divine harmony.